The Relationship between Music and Taboos in the Society of the Tao (An Indigenous Ethnic Group of Taiwan). (March 2013) - Lin, Wei-Ya
The Tao (chi. 達悟 or Yami 雅美) are one of the 14 officially recognized indigenous groups in Taiwan, who live on Orchid Island southeast of the main island of Taiwan. Their language is orally transmitted. The traditional music of the Tao primarily consists of songs, which are used as means for teaching and saving history, life stories and taboos of the Tao. Their songs carry all the wisdom gained from centuries of experience; they support the life of the Tao, their surviving in harmony with nature and they are necessary as tools for education of their traditions and heritage. How are taboos defined and what kind of function do taboos have in the society of Tao? How is the function of traditional songs related to the taboos? What kind of relationship do songs and taboos have in the society of Tao? I would like to discuss these questions in this article.